PENGARUH KUALITAS LAYANAN PENDIDIKAN TERHADAP KEPUASAN SISWA DI SMA MTA SURAKARTA TAHUN 2016 - Rizkan Faif Fasani; Harini Harini; Sunarto Sunarto (Department of Economics Education, Universitas Sebelas Maret, 2018)
This study aimed to test the influence of the quality of education services consisting of (1) the curriculum (2) teachers and (3) facilities (4) management of education (5) the cost of education (6) responsiveness and (7) access to facilities.The population in this study were students of class X and XI in SMA MTA Surakarta totaling 600 students. The sample in this study were 1 students were selected by random sampling technique sratified proportionate. This study uses quantitative methods with descriptive design. The data collection techniques implemented with a questionnaire to determine the level of influence the quality of educational services to the student satisfaction. Analysis of data using multiple regression techniques. The results of the study are as follows: the calculation results obtained using the F test probability value in the column Sig is 0,000, the value is less than 0.05. Ho then be rejected, which means a significant difference between the variable quality of educational services to the satisfaction of high school students MTA Surakarta (Y) simultaneously.The result of the calculation using t-test probability values obtained from the seventh variable is less than 0.05 and the value of t is greater than t table then can thus be concluded that Ho rejected, which means a significant difference between the variable quality of educational services to the satisfaction of high school students MTA Surakarta (Y) partially. Based on the regression equation Y = -8.278 + 0.047 X1 + 0.311 X2 + 0.194 X3 + 0.071 X4 + 0.266 X4+ 0.094 X6 + 0.315 X7 + €